Proposed Improvement of the Supplier Selection Process using Analytical Hierarchy Process (AHP) Method: A Case Study of Aircraft MRO in Indonesia - Abi Wafa; Yos Sunitiyoso (Pusat P2M Politeknik Negeri Batam, 2025)
Indonesia’s aviation industry has experienced rapid post-pandemic growth, with a 38.5% increase in passenger traffic in 2024 compared to 2022, positioning it as the largest and fastest-growing market in ASEAN. This expansion has intensified demand for Maintenance, Repair, and Overhaul (MRO) services. PT XYZ, Indonesia’s leading aircraft maintenance provider, faces procurement issues in acquiring painting materials, causing delays and missed turnaround targets. This study aims to optimize supplier selection through the Analytical Hierarchy Process (AHP), employing a mixed-methods approach involving stakeholder interviews to determine key criteria. The model incorporates six main criteria and fourteen sub-criteria, prioritizing quality, regulatory compliance, reliability, cost, and delivery. The results identified Supplier II as the most suitable option. The study recommends institutionalizing the AHP model within PT XYZ’s procurement policy and integrating it into its ERP system, offering a scalable solution for enhancing procurement efficiency and supporting strategic decision-making in aviation MRO operations.